2018
DOI: 10.1089/sur.2017.262
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Antimicrobials in Critically Ill Patients

Abstract: Critically ill patients with severe infections often have altered pharmacokinetic and pharmacodynamic variables that lead to challenging treatment decisions. These altered variables can often lead to inadequate dosing and poor treatment outcomes. The pharmacokinetic parameters include absorption, distribution, metabolism, and excretion. Pharmacodynamics is the relationship between drug serum concentrations and pharmacologic and toxicologic properties of the medication. In addition to these altered parameters, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
1
5
1
Order By: Relevance
“…The present study showed that the standard dosing of LNZ (600 mg q12h) for all patients led to subtherapeutic LNZ exposure in critically ill Chinese patients. The high variability and outside-the-target ranges of LNZ levels were in line with those in other studies on Caucasian patients [8,[20][21][22][23]. In this study, CrCL was identi ed as the most important covariate on the LNZ clearance, which is a comprehensive indicator including body weight, age, serum creatinine, and sex.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The present study showed that the standard dosing of LNZ (600 mg q12h) for all patients led to subtherapeutic LNZ exposure in critically ill Chinese patients. The high variability and outside-the-target ranges of LNZ levels were in line with those in other studies on Caucasian patients [8,[20][21][22][23]. In this study, CrCL was identi ed as the most important covariate on the LNZ clearance, which is a comprehensive indicator including body weight, age, serum creatinine, and sex.…”
Section: Discussionsupporting
confidence: 83%
“…Patients enrolled before October 30, 2018, were included in the model establishment group, and those enrolled after were included in the external validation group. The study protocol was designed according to the SPIRIT guideline [20]. All experiments were performed under the approved protocols, guidelines, and regulations, and all patients (or appropriate surrogates for patients unable to consent) provided written informed consent simultaneously.…”
Section: Study Design and Patientsmentioning
confidence: 99%
“…anti-infective drugs' PK parameters are commonly known to be influenced by multiple patient-related factors as well as some interferential supportive therapy. 25 For these reasons, we studied the The mortality rate (Table 2) in our study (1.2%) was lower than that found in other studies (4.1%). 20 Caspofungin prophylaxis and therapy were effective in 94.96% (132/139) and 80% (20/25), respectively ( For caspofungin, drug-drug interactions caused by enzyme inducers as well as some immunosuppressants have already been F I G U R E 4 Caspofungin trough concentrations under different conditions (weight ≤70 kg and weight ≥70 kg; with continuous renal replacement therapy (CRRT) before transplantation and without CRRT; with cyclosporine A and without cyclosporine A therapy; ALB ≤30 g/L and ALB ≥30 g/L).…”
Section: Discussioncontrasting
confidence: 47%
“…At present, no available studies support the use of echinocandins for prophylaxis among kidney transplant patients . Furthermore, anti‐infective drugs' PK parameters are commonly known to be influenced by multiple patient‐related factors as well as some interferential supportive therapy . For these reasons, we studied the efficacy and safety of caspofungin treatment and prophylaxis in the kidney transplant patients and evaluated the factors influencing caspofungin C min in kidney transplant patients.…”
Section: Discussionmentioning
confidence: 99%
“…The study protocol was planned in accordance with the SPIRIT guideline. 20 All experiments were conducted in compliance with the approved protocols, guidelines, and regulations, and all patients (or suitable surrogates for patients unable to consent) provided written informed consent. This study was approved by the Ethics Committee of Guangdong Provincial People’s Hospital, Nanfang Hospital, Guangzhou First People’s Hospital, and Guangzhou 999 Brain Hospital (Guangdong, China) (GDREC2018269H(R1)) and was carried out in compliance with the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%